GIS-based multi criteria decision making method to identify potential runoff storage zones within watershed - Vikas Kumar Rana; Tallavajhala Maruthi Venkata Suryanarayana (Annals of GIS, 2020)
ABSTRACTThe objective of this study was to identify potential runoff storage zones based on the various physical characteristics of the Vishwamitri watershed using a GIS-based conceptual framework that combines through analytic hierarchy process using multi criteria decision-making method. The conceptual framework will help to identify potential runoff storage zones for water storage sites based on the various physical characteristics (rainfall, slope, land use/land cover, height above the nearest drainage, stream order, curve number, topographic wetness index) of the watershed. It was found out that 17% of the area is optimally suitable, 33.2% of the area is moderately suitable, 33.1% of the area is marginally suitable and 18.7% of the area is not suitable for water storage zones/structures. Results will help concerned authorities in the proficient arrangement and execution of water-related plans and schemes, improve water shortage, reduce dependability on ground water and ensure sustainable water availability for local and agricultural purposes in the study area.